The importance of technical expertise for civil construction (Research, Society and Development, 2022)
Construction is an important player in the economies of developing countries. Engineering has sought to add new technologies, especially in the field of globalization, which increases competition. In addition to the need for innovation, the engineer has difficulty finding the right fit for the project, cost, quality and schedule, and the management success goal in these new scenarios. In this sense, this study aimed to report on the importance of the expert report for civil construction. This is a literature review research, with descriptive methodology, presented in a qualitative way. Data collection was performed through electronic search, in the Scientific Electronic Library Online (SCIELO) and Google Scholar databases. The theme in question was developed with the research focus focused on the study objective. From the growing development that the civil construction sector has been facing, as well as the emergence of new techniques and technologies, it can be guaranteed that, on the one hand, this area is gathering conditions to carry out more and more high-quality work. On the other hand, the field of construction suffers from great apprehensions, from the lack of quality of the projects to be executed to the lack of qualified labor for the execution of the buildings, this being, certainly, the most serious of the problems.